Unveiling the Relationship of Zoomer Generation Learning Preferences and Mathematical Conceptual Understanding - Maharani Maharani; Mutia Mutia; Anisya Septiana (Pendidikan Matematika STKIP Kusuma Negara, 2026)
This study aims to know relationship between Gen Z's mathematics learning preferences and their ability to understand mathematical concepts. The research method used a quantitative approach with a correlational study design. The research population consisted of 199 eighth-grade students at MTs Baitul Makmur, and through simple random sampling, a sample of 34 students. The instruments used were questionnaires and tests. The data analysis technique employed was the product-moment correlation test. The research results indicate that: (1) Gen Z students prefer learning in pairs (70.52%) and asking questions directly to the teacher (69.99%) while passive methods such as rewriting (51.17%) and listening to recordings (52.64%) are less preferred as they are considered less effective; (2) Gen Z students are fairly good at using mathematical steps (approximately 69.11%), but still struggle to understand the key aspects of the concepts (60.29%), so Gen Z students understand how it works more than its meaning; (3) There is a significant relationship between learning preferences (X) and mathematical concept understanding ability (Y), with a correlation coefficient of 0.629, thus falling into the category of a strong relationship. The coefficient of determination of 39.43% indicates that learning preferences contribute moderately to students' conceptual understanding ability.